2015
DOI: 10.2106/jbjs.n.01230
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Osteoporosis Screening— Gleaning Additional Information from Diagnostic Wrist CT Scans

Abstract: HU measurements can be obtained from any diagnostic CT scan using modern software programs and can be obtained by physicians in the office setting with minimal effort and at no additional cost or radiation exposure to the patient. Regardless of imaging indications, we suggest that patients with HU values below the identified thresholds be considered for further metabolic bone disease work-up, such as additional imaging, laboratory assessments, the initiation of osteoporosis treatment, or appropriate referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…However, this method of correlating HU with DEXA scores has been shown to be reliable. 7,8 Our distal radius and capitate bone density findings are comparable to those of Schreiber et al 8 Additionally, Todisco et al in 2005 19 showed that bone mineral density on CT scan directly correlated to bone volume on histomorphometry. Norton in 2001 20 showed that HU correlated with bone quality, and Ahlo in 1998 21 showed a significant correlation between HU and trabecular bone mineral density.…”
Section: Concentric Shellssupporting
confidence: 81%
See 1 more Smart Citation
“…However, this method of correlating HU with DEXA scores has been shown to be reliable. 7,8 Our distal radius and capitate bone density findings are comparable to those of Schreiber et al 8 Additionally, Todisco et al in 2005 19 showed that bone mineral density on CT scan directly correlated to bone volume on histomorphometry. Norton in 2001 20 showed that HU correlated with bone quality, and Ahlo in 1998 21 showed a significant correlation between HU and trabecular bone mineral density.…”
Section: Concentric Shellssupporting
confidence: 81%
“…3). Hounsfield units (HUs) were then measured in each region of the scaphoid to evaluate bone density using the method previously described by Schreiber et al 7,8 Bone density of the scaphoid proximal and distal poles, the distal radius, and the capitate was measured by averaging three axial sections proximal to the physeal scar in the distal radius and three cross sections in the carpal bones as described by Schreiber et al 7,8 Cortical regions were included in these measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that CT attenuation correlates with dual X-ray absorptiometry (DEXA) and that HU can serve as a surrogate measure for bone density, though it does not directly measure bone mineral content. (17,(21)(22)(23)(24)(25)(26)(27)(28)(29) In our study, we found age-related global bone density loss as measured by mean HU, which affected the CP as well as other craniofacial bones. This age-related bone loss appears to occur diffusely throughout the CP, however, this may be more profound in the middle CP, as compared to the posterior region.…”
Section: Discussionsupporting
confidence: 47%
“…DXA has been widely used for the diagnosis of osteoporosis. However, previous studies indicate that the majority of patients at high-risk of osteoporosis have not been adequately evaluated for BMD [ 13 , 14 ]. Therefore, various alternative tools for osteoporosis screening have been suggested.…”
Section: Discussionmentioning
confidence: 99%